2021
DOI: 10.1007/s11126-021-09962-3
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Wearing a Face Mask on the Psychiatric Interview: a National Survey During the COVID-19 Pandemic

Abstract: The COVID-19 pandemic has forced to rapidly encourage the use of face masks during medical consultations, with significant implication for psychiatry. This study examined the opinions and attitudes of psychiatrists toward the impact of wearing a face mask on the psychiatric interview. 513 psychiatrists and trainee psychiatrists completed an electronic survey about the impact of wearing a face mask on the psychiatric interview. Less efficiency in capturing clinical signs/symptoms, emergence of false inferences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 12 publications
2
7
0
Order By: Relevance
“…Overall, our study results confirm the hypothesis shared by many researchers that the negative consequences of the COVID-19 pandemic on people with mental disorders go far beyond the physical health impairments potentially caused by a SARS CoV-II infection [16,18,19,[21][22][23][24][25][26][27]. We found direct effects of a SARS CoV-II infection only for perceived negative effects on physical well-being and on mobility.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Overall, our study results confirm the hypothesis shared by many researchers that the negative consequences of the COVID-19 pandemic on people with mental disorders go far beyond the physical health impairments potentially caused by a SARS CoV-II infection [16,18,19,[21][22][23][24][25][26][27]. We found direct effects of a SARS CoV-II infection only for perceived negative effects on physical well-being and on mobility.…”
Section: Discussionsupporting
confidence: 90%
“…Among other vulnerable groups, persons with severe mental illness (SMI) have been expected by many experts to become particularly affected by the psychological distress caused by fear of infection, increasing social isolation, and restricted access to mental health care services [15][16][17][18][19][20][21][22][23][24][25][26][27]. However, most of the studies on the impact the COVID-19 pandemic on psychopathological symptoms suggested that the majority of patients with mental illness seemed to have adapted to the challenges of the pandemic after the first wave as well as people without pre-existing mental health problems [6,16,17,[28][29][30][31][32][33][34][35][36][37][38][39].…”
Section: Introductionmentioning
confidence: 99%
“…General telehealth studies have found that both patients and providers have high levels of satisfaction with the use of telehealth and are willing to use it in the future, finding it to be comparable in quality of care delivery, with increased flexibility and lower cost ( Andrews et al, 2020 ; Malouff et al, 2021 ). Within psychiatry specifically, TMH offers an opportunity to exchange verbal and non-verbal communication without masks, which have been reported to negatively impact the quality of the psychiatric evaluation( Dondé et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…But while we support research that interrogates core constructs, mechanisms and processes, we caution against inferring from studies that use broad approaches and examine more general concepts, and as such perhaps lack the necessary specificity. In this study, 1 for example, major depressive disorder (MDD) is widely recognized as a heterogeneous illness, and this would be even more likely in the patients described, given the naturalistic recruitment from treatment centres. Irritability itself, as we have pointed out 2 and the authors acknowledge, is variably characterized and in need of precise definition.…”
Section: Disclosurementioning
confidence: 99%
“…It has been well established that facial coverings significantly impact the quality and ease of psychiatric assessments. 1 Interviews conducted by clinicians whose mouths are hidden can create false inferences and beliefs in patients, worsen communication barriers, and erode therapeutic rapport. Facial coverings also hide micro-expressions and impede non-verbal expressions of empathy and active listening.…”
mentioning
confidence: 99%